2005
DOI: 10.2337/diacare.28.4.777
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Time Physical Activity Is Associated With Poor Glycemic Control in Type 1 Diabetic Women

Abstract: OBJECTIVE -We studied the association between leisure time physical activity (LTPA) and glycemic control, insulin dose, and estimated glucose disposal rate (eGDR) in type 1 diabetes. RESEARCH DESIGN AND METHODS-This is a cross-sectional study of 1,030 type 1 diabetic patients participating in the Finnish Diabetic Nephropathy Study, a nationwide multicenter study. LTPA was assessed by a validated 12-month questionnaire and expressed in metabolic equivalent (MET) units. Patients were grouped as sedentary (LTPA Ͻ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
4
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 37 publications
(12 reference statements)
3
55
4
2
Order By: Relevance
“…In CONCLUSIONS -Low LTPA was associated with a higher prevalence of the metabolic syndrome, supporting our previous findings on LTPA and insulin sensitivity in type 1 diabetes (14). Due to the cross-sectional study design, LTPA could have been reduced by exercise-limiting factors associated with the metabolic syndrome.…”
Section: Research Design Andsupporting
confidence: 73%
See 2 more Smart Citations
“…In CONCLUSIONS -Low LTPA was associated with a higher prevalence of the metabolic syndrome, supporting our previous findings on LTPA and insulin sensitivity in type 1 diabetes (14). Due to the cross-sectional study design, LTPA could have been reduced by exercise-limiting factors associated with the metabolic syndrome.…”
Section: Research Design Andsupporting
confidence: 73%
“…METHODS -Using a cross-sectional study design, 1,028 type 1 diabetic patients from the FinnDiane Study (3,14) with data on leisure-time physical activity (LTPA) and metabolic syndrome were studied. Patients with end-stage renal disease and/or cardiovascular events were excluded.…”
Section: Research Design Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with type 1 diabetes were recruited from the Finnish Diabetic Nephropathy (FinnDiane) study [27]. The healthy male volunteers were medical students.…”
Section: Study Groupsmentioning
confidence: 99%
“…We previously showed that sedentary women with type 1 diabetes have worse glycaemic control than those who achieve the general recommendations for regular physical activity [3]. However, no prospective epidemiological studies have assessed the level of physical activity and the development of diabetic microvascular complications in patients with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%